Comprehensive seismic evaluation of existing buildings using ASCE 41-17 standards - Rosyidah, Anis; Dinda, Tree Irma; Saputra, Jonathan; Sucita, I Ketut (Universitas Mercu Buana, 2025)
This study addresses the lack of comprehensive seismic evaluations for eight-story reinforced concrete buildings in high-seismic zones, such as Jakarta, using the ASCE 41-17 standard. The research evaluates the seismic performance of a 35-year-old office building through a tiered analysis approach, including Tier 1, Tier 2, and Tier 3. The study aims to identify structural deficiencies and propose retrofitting measures to meet modern seismic standards. Defects in soft story behavior and overturning stability were among the five and fourteen items in the Tier 1 assessment that showed noncompliance. In Tier 2, linear analysis revealed critical ductility demands, with Demand-to-Capacity Ratios (DCR) exceeding permissible limits in most structural elements. The nonlinear pushover analysis conducted in Tier 3 revealed an insufficient structural capacity to withstand high seismic loads. Maximum inter-story drifts in the X and Y directions were 2.321% and 2.319%, respectively, surpassing Life Safety standards. The findings indicate that the building's seismic performance falls between the Life Safety and Collapse Prevention levels, emphasizing the urgent need for retrofitting to enhance its resilience. This research presents a comprehensive framework for integrating global standards and local seismic conditions to enhance the safety and performance of existing structures in high-risk areas.